Correction: A Genetic Screen Identifies a Requirement for Cysteine-Rich-Receptor-Like Kinases in Rice NH1 (OsNPR1)-Mediated Immunity. - Mawsheng Chern (PLoS Genetics, 2016)
[This corrects the article DOI: 10.1371/journal.pgen.1006049.].